ISLAMIC MONETARY POLICY AND ITS IMPACT ON REAL SECTOR - Isnaeni Octaviani; Mohammad Nur Rianto Al Arif (TRIKONOMIKA, 2018)
The essence of the Islamic economic system is strengthening the real sector. This research aims to analyze the effect of Islamic monetary instrument (such as SBIS, PUAS and Islamic bank financing in the real sector. This research uses the Vector Error Correction Model (VECM) as a method of analysis. The finding revealed that based on the VECM estimation test, in the long term SBIS and Islamic bank financing has a positive effect on the Industrial Production Index (IPI). Meanwhile, PUAS has an adverse effect toward Industrial Production Index (IPI). Besides, based on impulse response function (IRF) test, the shock of SBIS and PUAS responded positively by Industrial Production Index (IPI). Then based on the result of FEVD test, the variable of PUAS in the model of this research has the most significant contribution toward Industrial Production Index (IPI).